2006
DOI: 10.1016/j.jacc.2006.02.045
|View full text |Cite
|
Sign up to set email alerts
|

Family History of Diabetes Is a Major Determinant of Endothelial Function

Abstract: Bioavailability of nitric oxide is lower in persons with a strong FH of T2D. Glycemic burden, even in the nondiabetic range, can contribute to endothelial dysfunction. Abnormalities of endothelial function may contribute to atherosclerosis before development of overt diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
71
2
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(82 citation statements)
references
References 20 publications
6
71
2
3
Order By: Relevance
“…Furthermore, our data seem to confirm that early and continuous aggressive treatment of glycemia is important to avoid future complications. Incidentally, in our opinion, the recent findings showing the existence of a continuum between the values of glycemia, endothelial dysfunction, and the risk of a cardiovascular event, even in nondiabetic patients, supports this concept (39,40).…”
Section: Ceriello and Associatesmentioning
confidence: 60%
“…Furthermore, our data seem to confirm that early and continuous aggressive treatment of glycemia is important to avoid future complications. Incidentally, in our opinion, the recent findings showing the existence of a continuum between the values of glycemia, endothelial dysfunction, and the risk of a cardiovascular event, even in nondiabetic patients, supports this concept (39,40).…”
Section: Ceriello and Associatesmentioning
confidence: 60%
“…13 In support of the consistent epidemiologic findings about family history, a wide range of metabolic studies have reported early signs of abnormalities among otherwise healthy people who have a family history of diabetes. Persons with a positive family history of diabetes, including children, might show early signs of defective insulin actions, [14][15][16][17][18] glucose intolerance, 19,20 lipid abnormalities, high BP, large weight gains, 21 reduced ␤-cell function, 20,22 impaired endothelial function, 23 and altered energy (mitochondrial) metabolism. [24][25][26][27] The epidemiologic evidence for the familial aggregation of CVD is also strong.…”
Section: Family History As An Independent Risk Factor For Type 2 Diabmentioning
confidence: 99%
“…Although this is not supported by strong scientific evidence, many observational studies have revealed its relationship with increased cardiovascular risk [21]. For instance, several workers have confirmed significant endothelial dysfunction in subjects with parental history of type 2 DM [26][27][28][29], although another study has reported a contrasting finding [30]. Nevertheless, an association between carotid intima-media thickness (CIMT) and risk factors for atherosclerosis has been documented by some investigators [31]; underscoring the role of family history of type 2 DM on development of cardiovascular risk.…”
Section: Obesity and Type 2 Diabetes Mellitus: The Nexusmentioning
confidence: 99%